Comparison of the tensile strength of FDM printed specimens with different infill densities made of PA12 and PA12+CF15 - Miazio, Łukasz (Technical Sciences, 2025)
The research presented in this article represents a further stage in studies on the strength of components printed using 3D printing technology, specifically FDM (Fused Deposition Modelling). The article presents the results of tensile strength tests on samples printed from PA12 and PA12+CF15 materials, while previous studies by the author focused on PLA material. Basic material data provided by manufacturers and distributors of materials used in the FDM method, such as tensile strength and Young’s modulus, refer to the most favourable model orientation during printing. However, in additive technologies, particularly FDM, the constructed object shows significant layering differences (in the Z direction). The direction of material deposition (in the XY plane) is also crucial. Additionally, the strength is influenced by the degree and type of infill within the model and the temperature during printing. For these reasons, it is essential to understand the relationship between technological parameters and the resulting strength for specific materials. This study aimed to determine the tensile strength of samples printed with varying infill percentages. In the context of the new material, PA12+CF15, it is essential to understand how the addition of carbon fibers affects the mechanical properties of prints compared to traditional materials, such as PA12 and PLA. Carbon fibers can significantly increase the strength and stiffness of the composite, potentially leading to applications in producing parts with high strength requirements. Therefore, studying the strength of materials concerning various printing parameters is crucial for developing the potential of FDM technology and its industrial applications. PA12+CF15 is composed of polyamide 12 (PA12), a thermoplastic material with good chemical resistance, abrasion resistance, and flexibility. The addition of 15% carbon fibers (CF15) reinforces the composite structure, leading to increased stiffness, mechanical strength, and deformation resistance. The study shows that this addition enhances PA12’s strength by approximately 13%, also facilitating printing by reducing shrinkage.